Major bacterial isolate and antibiotic resistance from routine clinical samples in Southern Ethiopia - Mengistu Hailemariam; Tsegaye Alemayehu; Bereket Tadesse; Netsanete Nigussie; Asnakech Agegnehu; Techilo Habtemariam; Mulubrhan Ali; Enkosilassie Mitiku; Elshaday Azerefegne (Scientific Reports, 2021)
Abstract Currently, antibiotic-resistant bacterial infections are a challenge for the health care system. Although physicians demand timely drug resistance data to guide empirical treatment, local data is rather scarce. Hence, this study performed a retrospective analysis of microbiological findings at the Hawassa public hospital. Secondary data were retrieved to assess the prevalence and level of drug resistance for the most common bacterial isolates from clinical samples processed at Hawassa University Comprehensive Specialized Hospital. Out of 1085 clinical samples processed in the microbiology laboratory, the prevalence of bacterial infection was 32.6%. Bacterial bloodstream infection was higher in children than in adults (OR, 4; 95% CI 1.8–14.6; p = 0.005). E. coli and K. pneumoniae were the commonest bacterial isolate both in children (36.8%, 26.3%) and in adults (33.3%, 26.7%) from the urine sample while, the leading bacteria identified from the CSF sample was P. aeruginosa, 37% in children and 43% in adult. In this study, all identified bacterial isolates were multi-drug resistant (MDR) ranging from 50 to 91%. The highest proportion of MDR was S. aureus 91.1 followed by K. pneumoniae 87.6%. Since the nationwide investigation of bacterial isolate, and drug resistance is rare in Ethiopia, a report from such type of local surveillance is highly useful to guide empirical therapy by providing awareness on the level resistance of isolates.